Synthesis, structure and optical properties of cerium-doped calcium barium phosphate – a novel blue-green phosphor for solid-state lighting. Issue 1 (12th November 2014) - Komuro, Naoyuki; Mikami, Masayoshi; Shimomura, Yasuo; Bithell, Erica G.; Cheetham, Anthony K.
Abstract : A new blue-green phosphor, Ca6 BaP4 O17 :Ce 3+, which can be prepared by conventional solid-state synthesis, is reported as a candidate phosphor for solid-state lighting with near-ultraviolet LEDs. Abstract : A new blue-green phosphor, Ca6 BaP4 O17 :Ce 3+, which can be prepared by conventional solid-state synthesis, is reported as a candidate phosphor for solid-state lighting with near-ultraviolet LEDs. Under excitation at around 400 nm, Ca6 BaP4 O17 :Ce 3+ shows strong blue-green emission with the peak position at 477 nm. Ce 3+, Si 4+ co-doping is found to enhance the luminous intensity, and the unique emission characteristics of this combination are studied and related to the crystal structure. Ca6 BaP4 O17 is an exceptional host material, which also accommodates Eu 2+, emitting strong yellow light under 400 nm excitation. A fabricated white LED, combining Ca6 BaP4 O17 :Ce 3+, Si 4+ with Ca6 BaP4 O17 :Eu 2+ and a red CaAlSiN3 :Eu 2+ phosphor, achieved a luminous efficacy of 45 lm W −1 with a color-rendering index of 93 around the correlated color temperature of 4500 K.